Getting the chemistry right: protonation, tautomers and the importance of H atoms in biological chemistry. Issue 2 (1st February 2017) - Bax, Ben; Chung, Chun-wa; Edge, Colin
Abstract : H atoms are `hard to see' in X‐ray crystal structures of protein–ligand complexes. This paper discusses the problem of identifying the correct tautomeric form(s) of protein‐bound ligands. Abstract : There are more H atoms than any other type of atom in an X‐ray crystal structure of a protein–ligand complex, but as H atoms only have one electron they diffract X‐rays weakly and are `hard to see'. The positions of many H atoms can be inferred by our chemical knowledge, and such H atoms can be added with confidence in `riding positions'. For some chemical groups, however, there is more ambiguity over the possible hydrogen placements, for example hydroxyls and groups that can exist in multiple protonation states or tautomeric forms. This ambiguity is far from rare, since about 25% of drugs have more than one tautomeric form. This paper focuses on the most common, `prototropic', tautomers, which are isomers that readily interconvert by the exchange of an H atom accompanied by the switch of a single and an adjacent double bond. Hydrogen‐exchange rates and different protonation states of compounds ( e.g. buffers) are also briefly discussed. The difference in heavy (non‐H) atom positions between two tautomers can be small, and careful refinement of all possible tautomers may single out the likely bound ligand tautomer. Experimental methods to determine H‐atom positions, such as neutron crystallography, are often technically challenging. Therefore, chemical knowledge and computational approaches are frequently used in conjugation with experimental data to deduce the bound tautomer state. Proton movement is a key feature of many enzymatic reactions, so understanding the orchestration of hydrogen/proton motion is of critical importance to biological chemistry. For example, structural studies have suggested that, just as a chemist may use heat, some enzymes use directional movement to protonate specific O atoms on phosphates to catalyse phosphotransferase reactions. To inhibit `wriggly' enzymes that use movement to effect catalysis, it may be advantageous to have inhibitors that can maintain favourable contacts by adopting different tautomers as the enzyme `wriggles'.